2013
DOI: 10.2174/1573403x113099990031
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial QRS-T Angle: Implications in Clinical Practice

Abstract: The ventricular gradient (VG) as a concept was conceived in the 1930s and its calculation yielded information that was not otherwise obtainable. The VG was not utilized by clinicians at large because it was not easy to understand and its computation time-consuming. The contemporary spatial QRS-T angle is based on the concept of the VG and defined as its mathematical and physiological integral. Its current major clinical use is to assess the cardiac primary repolarization abnormalities in 3-dimensional spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 130 publications
(215 reference statements)
1
65
0
3
Order By: Relevance
“…DISCUSSION QRS-T angle, described as the angle between the mean QRS and T vectors, reflects the main orientation of electrical heart activity during ventricular depolarization and repolarization. A wider QRS-T angle indicates an abnormal set of ventricular repolarization and is considered as a novel risk marker for cardiovascular morbidity and mortality compared to other traditional cardiovascular risk factors and ECG risk parameters [2]. Recent studies demonstrated that hypertension and CAD were probably the main underlying pathophysiological conditions for an abnormal QRS-T angle [3][4][5] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION QRS-T angle, described as the angle between the mean QRS and T vectors, reflects the main orientation of electrical heart activity during ventricular depolarization and repolarization. A wider QRS-T angle indicates an abnormal set of ventricular repolarization and is considered as a novel risk marker for cardiovascular morbidity and mortality compared to other traditional cardiovascular risk factors and ECG risk parameters [2]. Recent studies demonstrated that hypertension and CAD were probably the main underlying pathophysiological conditions for an abnormal QRS-T angle [3][4][5] .…”
Section: Resultsmentioning
confidence: 99%
“…It is described as the angle between the main electrical axes of ventricular depolarization and repolarization [1]. Previous studies in literature showed that hypertension and coronary artery disease (CAD) may cause a widened QRS-T angle on electrocardiogram (ECG) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…[62][63][64] This kind of relationship between QRS-T angle and cardiac autonomic neuropathy may suggest structural, functional, and electrical imbalance. 65 Furthermore, spatial QRS-T angel >45-50 degrees in T2DM increased the risk of incidents of cardiovascular disease by 114% total mortality increase by two folds 33 and the morbidity of silent myocardial infarction by 19%. 66 Although FQRSTA derived from planar ECG and spatial vector may be used to estimate the prognosis and morbidity of cardiac diseases mentioned above; we have not yet analyzed the influence of FQRSTA from Holter on prognosis or diagnosis of cardiac diseases in this study.…”
Section: Dm and Fqrstamentioning
confidence: 99%
“…76 Meanwhile, the QRS-T angle depended on heterogeneity and dynamical change of the action potential duration in myocardial cells, and its gradients of transmural, apicobasal, and leftright ventricle. 65 The potentially pathophysiological mechanisms of planar QRS and T vector change were induced by the risks of multiple levels and factors, including DM, lipid metabolism, cardiac electrical disturbance, and smoking, which thus caused adverse cardiac structure, functional and autonomic change, and imbalance.…”
Section: Underlying Mechanisms Of Qrs and T Vector Change In Dmmentioning
confidence: 99%
“…Indeed, Yamasaki et al found that, for a mainly male clinical population, it was the most significant predictor of cardiovascular mortality [3]. In their 2013 review, Voulgari et al published a table summarising the studies on the prognostic value of this measurement on cardiovascular morbidity and mortality [4]. They concluded that the spatial QRS-T angle is an important prognostic predictor and that it is superior to more conventional ECG parameters.…”
Section: Introductionmentioning
confidence: 99%